2023
DOI: 10.3390/educsci13030228
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality as the Catalyst for a Novel Partnership Model in Initial Teacher Education: ITE Subject Methods Tutors’ Perspectives on the Island of Ireland

Abstract: This small-scale study explores the attitudes of fifty initial teacher education (ITE) subject methods tutors towards the use of virtual reality (VR) in education and considers whether VR could be a catalyst for reviewing the partnership model within ITE programmes. In addition, this study offers a novel solution to ITE tutors’ challenges when managing their own technological and pedagogical development alongside preparing student teachers for technology-enhanced learning (TEL). Building on previous research o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…In turn, the study reports that the existence of technical support for emerging technologies contrib improving companies' strategy and progress. In addition, the study of [45] show The fact that VR as a business strategy exerts a significant influence on the willingness to invest in technology also seems to be in line with the study of [41]. According to their results, the perception of VR as a business strategy is an important determinant of the intention to adopt VR.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…In turn, the study reports that the existence of technical support for emerging technologies contrib improving companies' strategy and progress. In addition, the study of [45] show The fact that VR as a business strategy exerts a significant influence on the willingness to invest in technology also seems to be in line with the study of [41]. According to their results, the perception of VR as a business strategy is an important determinant of the intention to adopt VR.…”
Section: Resultssupporting
confidence: 72%
“…In turn, the study of [44] reports that the existence of technical support for emerging technologies contributes to improving companies' strategy and progress. In addition, the study of [45] showed that technical assistance is a crucial factor for companies' adoption of virtual mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The integration of learning technologies in the field of interaction design education holds significant potential for improving learning outcomes and preparing students for real-world design challenges. By leveraging technology-enhanced pedagogies, educators can create immersive and interactive learning experiences that closely mirror industry practices (Wu et al, 2023;Cowan, & Farrell, (2023).…”
Section: Application Of Learning Technologies In Interaction Design E...mentioning
confidence: 99%
“…During the COVID-19 lockdown, research by Farrell [38] revealed a shift in the cooperating teacher/student teacher hierarchy, positioning student teachers as mentors or 'learning leaders', supporting experienced teachers in schools as they transitioned to new pedagogies associated with online teaching. This state of 'reverse mentoring' involved a reciprocal relationship between experienced and novice teachers, with dual mentoring in opposite directions, facilitated by student teachers' use of technology-enhanced learning and co-operating teachers' pedagogical mastery in the classroom [39,40].…”
Section: Theoretical Frameworkmentioning
confidence: 99%